4CMenB vaccine and its role in preventing transmission and inducing herd immunity. (2nd January 2022) - McMillan, Mark; Marshall, Helen S; Richmond, Peter
ABSTRACT: Introduction: Vaccination is the most effective method of protecting people from invasive meningococcal disease (IMD). Of all the capsular groups, B is the most common cause of invasive meningococcal disease in many parts of the world. Despite this, adolescent meningococcal B vaccine programs have not been implemented globally, partly due to the lack of evidence for herd immunity afforded by meningococcal B vaccines. Areas covered: This review aims to synthesize the available evidence on recombinant 4 CMenB vaccines' ability to reduce pharyngeal carriage and therefore provide indirect (herd) immunity against IMD. Expert opinion: There is some evidence that the 4CMenB vaccine may induce cross-protection against non-B carriage of meningococci. However, the overall body of evidence does not support a clinically significant reduction in carriage of disease-associated or group B meningococci following 4CMenB vaccination. No additional cost-benefit from herd immunity effects should be included when modeling the cost-effectiveness of 4CMenB vaccine programs against group B IMD. 4CMenB immunization programs should focus on direct (individual) protection for groups at greatest risk of meningococcal disease. Future meningococcal B and combination vaccines being developed should consider the impact of the vaccine on carriage as part of their clinical evaluation.